Adolescents somatic development in accordance with biological growth rate - Khodinow, Wladimir; Sitowski, Andriy; Savchuk, Igor (Publisher of the journal: Justyna Banas Laardo ''QUAUTY NEWS'', 2013)
There have been revealed significant correlation relations between anthropometric parameters and both chronological and biological age among boys and girls. But there have been set more consistent correlations of these indices with the biological age compared with the chronological one except for body length and chest girth among girls. It is determined that among girls and boys there has been a reliable correlation of body weight componential composition parameters with both chronological and biological age except for the absolute fat component of body weight among boys. While comparing the correlation coefficients of body weight componential composition parameters with both biological and chronological age there has been determined a closer correlation of these indices with biological age among boys andgirls. Such absolute and relative indices of body weight fat component among boys and absolute fat, muscle and bone body weight component among girls are statistically significant.
Keywords: Adolescents; somatic development; biological growth rate